Plant 5S rDNA has multiple alternative nucleosome positions - Fulnecek, Jaroslav; Matyasek, Roman; Kovarik, Ales (Genome, 2006)
In plants, 5S ribosomal DNA (5S rDNA) is typically found in hundreds of copies of tandemly arranged units. Nucleotide database searches revealed that the majority of 5S genes (>90%) have repeat lengths that are not simple multiples of a plant nucleosomal unit, ranging in plants from 175-185 bp. To get insight into the chromatin structure, we have determined positions of nucleosomes in the Nicotiana sylvestris and Nicotiana tomentosiformis 5S rDNA units with repeat lengths of about 430 and 645 bp, respectively. Mapping experiments carried out on isolated nucleo somal DNA revealed many (>50) micrococcal nuclease cleavage sites in each class of repeats. Permutation analysis and theoretical computer prediction showed multiple DNA bend sites, mostly located in the nontranscribed spacer region. The distance between bend sites, however, did not correspond to the average spacing of nucleosomes in 5S chromatin (approximately 180 bp). These data indicate that 5S rDNA does not have fixed nucleosomal positioning sites and that units can be wrapped in a number of alternative nucleosome frames. Consequently, accessibility of transcription factors to cognate motifs might vary across the tandem array, potentially influencing gene expression.
Keywords: Chromatin; Computer Simulation; Nicotiana; počítačová simulace; nukleozomy; ribozomální DNA; DNA, Ribosomal; tabák; DNA, Plant; Nucleosomes; chromatin; DNA rostlinná